The Rhodium Catalysed Direct Conversion of Phenols to Primary Cyclohexylamines. Issue 17 (19th July 2018) - Tomkins, Patrick; Valgaeren, Carlot; Adriaensen, Koen; Cuypers, Thomas; Vos, Dirk E. De
Abstract: Cyclohexylamines are important intermediates in chemical industry, which are currently produced from petrochemical sources. Phenols, however, are an attractive sustainable feedstock. We here demonstrate the transformation of phenols with ammonia to primary cyclohexylamines. In contrast to previously reported chemistry which used palladium catalysts, we here show that rhodium is an excellent catalyst for the formation of primary cyclohexylamines. Different parameters were studied and it was shown that the reaction is applicable to a scope of phenolic compounds providing high selectivity. Abstract : Oh, what a night ! Phenols are an attractive sustainable feedstock for cyclohexylamine synthesis. We here demonstrate the transformation of phenols with ammonia to primary cyclohexylamines. In contrast to previously reported chemistry which used palladium catalysts, we here show that rhodium is an excellent catalyst for the formation of primary cyclohexylamines. Different parameters were studied and it was shown that the reaction is applicable to a scope of phenolic compounds.